2006
DOI: 10.1111/j.1365-2850.2006.00971.x
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ experiences of collaboration with community healthcare professionals

Abstract: Over the last decades there has been a reduction in the number of institutional beds in psychiatric care in Norway. This has led to more psychiatric patients being dependent on community care and consequently an increased need for collaboration with the parents of these patients. In most cases parents are an important source of support in helping patients manage their everyday life. The aim of this study was to explore how parents of adult psychiatric patients experience collaboration with health professionals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 11 publications
2
40
2
Order By: Relevance
“…A clear rationale for family involvement and the specific role of the relative is also crucial. Research has demonstrated that whilst family members desire more involvement and education [7] they can feel that health professionals' focus on encouraging service user autonomy renders them powerless and without a role [28]. Our study demonstrates that preserving autonomy and privacy is bidirectional and similarly important for service users and relatives and is another potential barrier to involving relatives in relapse prevention planning.…”
Section: Discussionmentioning
confidence: 78%
“…A clear rationale for family involvement and the specific role of the relative is also crucial. Research has demonstrated that whilst family members desire more involvement and education [7] they can feel that health professionals' focus on encouraging service user autonomy renders them powerless and without a role [28]. Our study demonstrates that preserving autonomy and privacy is bidirectional and similarly important for service users and relatives and is another potential barrier to involving relatives in relapse prevention planning.…”
Section: Discussionmentioning
confidence: 78%
“…Parents of children with a mental illness look to mental health services for support, affirmation, and collaboration (Jakobsen & Severinsson 2006; Scharer 2002; Tarico et al . 1989), but the evidence suggests they are frequently disappointed, especially when a hospital admission is involved (Sarajärvi et al .…”
Section: Introductionmentioning
confidence: 99%
“…SPs need information, education, support, practical advice on managing the illness, and someone to listen to them (Gavois, Paulsson, Fridund, 2006;Jakobsen & Severinsson, 2006;Jubb & Shanley, 2002;Kim & Salyers, 2008;Marshall & Solomon, 2000;McAuliffe et al, 2009;Rose, 1998;Smith, 2003).…”
Section: Background Literaturementioning
confidence: 99%